Konsep Multiakad dalam Fatwa DSN-MUI: Sebuah Inovasi dalam Praktik Keuangan Syariah di Indonesia - Arridho Abduh; Asmuni Asmuni; Tuti Anggraini (Lembaga penelitian dan pengabdian kepada masyrakat, 2023)
This article discusses the concept of hybrid contracts in Fatwa DSN-MUI which is an innovation in Islamic financial practice in Indonesia. The hybrid contracts concept is an approach that combines several Islamic contracts or financial instruments in one transaction to achieve the goals desired by the parties involved. This paper outlines various examples of the application of hybrid contracts in Islamic financial transactions. This article provides an overview of how the hybrid contracts concept became an innovation in Islamic financial practice in Indonesia. By using hybrid contracts, financial actors can achieve their goals in a sharia manner and minimize the risks associated with such transactions. However, a good understanding of sharia principles and guidance from authoritative institutions such as DSN-MUI is still needed to maintain the integrity and validity of sharia transactions.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//